2017
DOI: 10.1097/mlr.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Iraq and Afghanistan Veterans’ Use of Veterans Health Administration and Purchased Care Before and After Veterans Choice Program Implementation

Abstract: There was low uptake of VCP services in the first year of the program. Data from additional years are needed to better understand the impact of this policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Previous research involving semi-structured interviews with VA key stakeholders (i.e., administrators, Veterans, pharmacists) and surveys with community providers during initial implementation of the Choice Program found similar problems regarding care fragmentation, 6,8 inadequate sharing of medical records, 8,17 administrative burdens for VA staff when dealing with community specialists' prescriptions, 7 prescription delays, 10 community specialist participation barriers, 17,18 and lack of provider role clarity associated with the Choice Program. 8 Our study shows, first, that these problems persist and, second, how they affect VA PCPs' experiences with referring patients to community specialty care.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous research involving semi-structured interviews with VA key stakeholders (i.e., administrators, Veterans, pharmacists) and surveys with community providers during initial implementation of the Choice Program found similar problems regarding care fragmentation, 6,8 inadequate sharing of medical records, 8,17 administrative burdens for VA staff when dealing with community specialists' prescriptions, 7 prescription delays, 10 community specialist participation barriers, 17,18 and lack of provider role clarity associated with the Choice Program. 8 Our study shows, first, that these problems persist and, second, how they affect VA PCPs' experiences with referring patients to community specialty care.…”
Section: Discussionmentioning
confidence: 95%
“…However, since its rollout, the Choice Program has faced challenges due to the rapid 90-day implementation period, ongoing refinements to the eligibility criteria, and delays with paying claims. 2 Previous literature summarizes the rollout of the Choice Program 5 and research findings on early implementation challenges with Veteran utilization, 6 pharmacy use, 7 women's health care coordination, 8 community specialist interest, 9 and hepatitis C care. 10 Yet none of these studies assessed the viewpoints of referring VA primary care providers (PCPs), who play a central role coordinating care 11 between the VA and community providers and were on the frontline during the implementation of the Choice Program.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing prevalence of ESRD among veterans and VA priorities to improve veterans' access to care, assessing the consequences of the VA Health Care System's "make versus buy" decision-making process for dialysis care is critically important. 30 The tradeoffs of "making" more VA dialysis care must be balanced against the tradeoffs of "buying" outpatient dialysis care from providers in the private sector as well as potential savings in VA dollars related to other medical care. Our findings suggest considerations of both the clinical consequences and operational realties of effective and efficient provision of dialysis services to veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evaluations of Choice showed that only 2-13% of eligible Veterans received health care through Choice in its first year of implementation. 3,4 Those Veterans who did use Choice still reported barriers related to pre-authorization and scheduling, inadequate provider networks, and liability for treatment costs. 3,5 Veteran experiences with Choice and VA health care during the initial rollout of this new program are largely unknown.…”
Section: Introductionmentioning
confidence: 99%